2018
DOI: 10.1155/2018/9364757
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage Rate, Antimicrobial Susceptibility Pattern, and Associated Factors of Staphylococcus aureus with Special Emphasis on MRSA among Urban and Rural Elementary School Children in Gondar, Northwest Ethiopia: A Comparative Cross-Sectional Study

Abstract: Introduction Staphylococcus aureus is a Gram-positive, catalase-positive, and coagulase-positive bacterial species commonly found on the skin and in the nose of most healthy individuals. The anterior nares of nose are the most frequent carriage sites for S. aureus in both adults and children. Methicillin resistance among S. aureus isolates has steadily increased worldwide. Objective The main objective of this study was to determine nasal carriage rate, antimicrobial susceptibility pattern, and associated risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
5
24
6
Order By: Relevance
“…Results from this study indicated that the nasal carriage rates for S. aureus among the participants was 22.9%, a rate signi cantly higher than that reported from studies from Thika Hospital, Kenya (8.9%), Nigeria (18.3%), and China (2.4%) ( (30). The difference in the various ndings would have been attributed to the sample size used giving the different studies a better power to detect the S. aureus nasal carriage.…”
Section: Prevalence Of S Aureus Nasal Carriagecontrasting
confidence: 62%
“…Results from this study indicated that the nasal carriage rates for S. aureus among the participants was 22.9%, a rate signi cantly higher than that reported from studies from Thika Hospital, Kenya (8.9%), Nigeria (18.3%), and China (2.4%) ( (30). The difference in the various ndings would have been attributed to the sample size used giving the different studies a better power to detect the S. aureus nasal carriage.…”
Section: Prevalence Of S Aureus Nasal Carriagecontrasting
confidence: 62%
“…However, it is important to note that the resistance profiles among countries would depend on the different practices of antibiotic use between the countries, antibiotic stewardship and enforcement of infection control practices. Overall, clindamycin, rifampicin, vancomycin and linezolid were the most effective antibiotics in this study, in contrast to findings from Ethiopia where gentamicin and ciprofloxacin were the most effective among isolates from primary school children [34].…”
Section: Discussioncontrasting
confidence: 99%
“…0.8%-1.5%)[4,33] and developing countries (e.g. 2.3%, 14/622 for urban/rural school children in Gondar, Ethiopia[34]; 0.6%, 85/950 for adult inpatients in a Kenyan government hospital[35]). However, the study populations are diverse making direct comparisons difficult.Several factors could be responsible for the high MRSA carriage rate in Ugandan children e.g.…”
mentioning
confidence: 99%
“…Our nding was also similar to those reported from other countries [18][19][20] . However, the nasal carriage rate of S. aureus in this study tends to be lower than that reported in Nigeria (56.3%), India (46.67%), United State of America (39.6%; age group 1-19 years old), Netherland (36%; age group 1-19 years, and Nepal (31%; age group less than 15 years old) [21][22][23][24][25] .…”
Section: Discussionsupporting
confidence: 92%